Tipe Teks dan Penerjemahan - Indah Sari (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
One of the procedures conducted by a translator is text analysis. It is aimed to find out the text type of the source text. Traditionally, a text type is determined by the topic, form, and the language used. However, it does not applicable to a text like science-fiction text. It is difficult for the translator to decide the text type. Therefore, Reiss (1971) gave the solution by determining the text type from its function. There are three types of text proposed by Reiss; they are informative, expressive, and operative.Â  Although a text may have more than one function, the translator just needs to see which function dominated the text. Text type is the important basic for the translator before producing a target text. He may produce the same or even different texts type depending on his translation purpose.